FLOT Neoadjuvant Chemotherapy Followed by Laparoscopic D2 Gastrectomy in the Treatment of Locally Resectable Advanced Gastric Cancer. (30th May 2020) - Zhang, Shun; Yan, Dongyi; Sun, Qi; Du, Tao; Cao, Dongliang; Yang, Yao; Yuan, Biao; Li, Haiqiang; Jiang, Xiaohua; Song, Chun
Abstract : Background . The prognosis of patients with advanced gastric cancer remains unsatisfactory, highlighting the need for improved therapeutic strategies. We analyzed 23 resectable advanced gastric cancer patients who received FLOT followed by laparoscopic gastrectomy with D2 lymphadenectomy to evaluate the efficacy and safety. Methods . Patients aged 18–75 years with gastric adenocarcinoma (stage cT3–4 and/or N + M0) underwent neoadjuvant FLOT therapy (four preoperative and four postoperative 2-week cycles) at Shanghai East Hospital. Laparoscopic gastrectomy was scheduled 3-4 weeks after completion of the last cycle of preoperative chemotherapy. The type of surgical procedure was determined by the location and extent of the primary tumor. Results . 23 patients were reviewed in the study. 20 patients (81.2%) received four courses of FOLT therapy, while 3 patients (18.8%) received three courses of treatment. There were 3 (13.0%) complete responses, 13 (56.5%) partial responses, 4 (26.1%) of stable disease, and 1 (4.3%) of progressive disease. The clinical efficacy response rate was 69.6%. The R0 resection rate was 91.3%. Only one patient exhibited grade III postoperative complications. The pathologic complete remission was 13%. The common grade 3/4 adverse events from chemotherapy were leucopenia (17.4%), neutropenia (30.4%), anemia (13%), anorexia (13%), and nausea (17.4%). Postoperative complications occurred in 5 patients (26.1%). There was no treatment-related mortality or reoperation. The most reason for not completing chemotherapy was the patient's request. Conclusions . These findings suggest that FLOT neoadjuvant chemotherapy, followed by laparoscopic D2 gastrectomy, is effective and safe in advanced, resectable advanced gastric cancer.